Engaging the Highly Skilled Diaspora in Home Country Development through Knowledge Exchange: Concept and Prospects - Sheila V. Siar (Philippine Institute for Development Studies (PIDS), 2013)
Strong negative reactions have been raised against the continuing and steadily increasing migration of highly skilled people from developing countries. There is, however, growing evidence that this outflow of skills and knowledge may not necessarily mean a loss for sending countries based on the concept of knowledge exchange and circulation. This concept argues that any apparent loss of skills and knowledge can be restored through the exchange or circulation of knowledge and skills between the highly skilled diaspora and their home country. Studies of transnationalism and diaspora have further emphasized the ways in which migrants can remain not only connected but also deeply committed to development processes in their home countries. Knowledge exchange poses a lot of potential for a number of reasons: the advances in communication and transportation technologies which reduce cross-border distance; the growing appreciation by governments of the network approach as a conceptual guide and strategy to thrive in a globalized world; and the increasing desire of migrants to connect with their home countries.The three cases (China, India, Philippines) presented in this paper show the wealth of knowledge assets that the highly skilled diaspora can contribute: as source of expertise in terms of skills, technologies, and markets; as source of venture capital; and as intermediary or middle person in providing language skills, cultural know-how, and contacts for building business relationships or collaborative projects. However, as these cases also show, the success of tapping the intellectual, economic, and social capital of the diaspora depends on consistent, well-defined, and well-supported policies and programs.
Keywords: 330; Philippines; knowledge exchange; knowledge circulation; diaspora model; transnationalism